A mediação pedagógica como elemento potencializador dos processos de aprendizagem e desenvolvimento infantis - Moraes, Fabiana Aparecida de (2009)
Promoting Primary Education which provides children with thorough development requires the approach of knowledge, attitude and values in training professional educators who act at this level of teaching. Taking into consideration the premise that all the learning which takes place during childhood stays with us throughout life, it is important to observe the assistance that young learners have been receiving during such a period in Primary Education institutions in order to better understand the childish actions which take place in these places and how the children s development have been approached. The present work is the product of a field research carried out at a Primary Education institution in the city of Araraquara in São Paulo, which was accomplished so as to check if and how the mediation work of the teachers during the games take place as well as their contribution to the children s development. Therefore, the attempt was to identify how the professionals involved in this context conceive the play a game idea and their approach towards the kids when they are engaged in such an activity. The methodological procedures adopted in this work consisted of observations and interviews. The observations were carried out both when the children were in the classroom with the teacher and when they were doing free activities in the playground. Some interventions took place during the observations when the children were playing. Afterwards, interviews with the preschool children (3 to 6 years old) were carried out, who were asked about their idea of playing, the games they play and the places where these games take place. Furthermore, we also carried out interviews with the teachers and the educational agents, who are the people who attend the children throughout the period in which they stay at the institution. The methodological and theoretical reference on which this work was based was the Historical and Cultural theory by Vigotsky, which supported the data collection and analysis. The most significant results which were obtained show that the teachers assume a passive posture towards the possible mediation opportunities, thus restricting their acting to the explanation of a certain rule to the game or pulling the kids apart in case of conflicts. Considering the actions performed by the researcher during the games, it was possible to check that the main mediation opportunities should be based on constant observation, which is an important instrument to achieve mediations which are appropriate to the learning needs of the children. The importance of a deeper theoretical training for the teachers should also be highlighted, one which not only contributes to the games at the school day-to-day , but also so that these moments are legitimated through intentional mediations in order to promote an effective and thorough development of the children.